Clustering of progress curves of late blight for tomato genotypes from interspecific crosses - Fiorini, Cibelle Vilela Andrade; Silva, Derly José Henriques da; Silva, Fabyano Fonseca e; Mizubuti, Eduardo Seiti Gomide; Alves, Daniel Pedrosa; Cardoso, Tiago de Sá (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to estimate the progress curves of late blight in tomato genotypes, and to identify tomato genotype groups resistant to this disease. Twenty-five hybrid tomatoes, originated from crosses between four fresh market cultivars, one access from the Banco de Germoplasma de Hortaliças (BGH) of Universidade Federal de Viçosa (UFV), and five F8 lines (Solanum lycopersicum x Solanum habrochaites), selected as late blight resistance source, were evaluated. Plants were inoculated with a sporangium mixture of Phytophthora infestans, and then, six evaluations for late blight severity were carried out every three days. The exponential model was fitted to the data of late blight severity percentage, and the obtained parameter estimates – initial incidence of disease (yo )and progress rate of disease (r) – were submitted to the multivariate analysis of variance (Manova). The means of these estimates, obtained for each genotype, were submitted to the cluster analysis. An optimal number of eight distinct groups was observed, which made it possible to identify the genotypes belonging both to the resistant and susceptible groups. The experimental hybrids Ikram x 73 A, Nemo-Netta x 133 A, Ikram x 163 A and Nemo-Netta x 163 A showed the smaller rate of disease progress and, therefore, higher late blight resistance.